Incorporation of Krik Slamat Values In The Exercise Of Rights Over Customary Land - Dianto, Dianto (Law and Justice, 2023)
Pembadanan nilai dengan metode asli masyarakat adat menampakan nilai bukan hanya terlihat namun juga terasa yang berbeda dengan pembadanan nilai dengan metode negara yang justru nilai asli mengalami reduksi. Artikel ini bertujuan menganalisis pembadanan nilai ’krik slamat’ pada penguasaan hak atas tanah adat. Metode penelitian yang digunakan adalah metode penelitian nondoktrinal dengan pendekatan antropologi hukum dan pendekatan konseptual. Artikel ini menunjukan 1) Nilai krik slamat  merupakan asas hukum berdimensi ketuhanan ‘religio magis’  menjadi pijakan dasar pembentukan hukum adat (pulung), 2) Pembadanan nilai ‘krik slamat’ ke dalam hukum adat dilakukan dengan metode ‘pera telu’ yang wujudnya nilai tersebut tetap tampak dan terasa di dalam asas hukum dan norma hukum adat terkait penguasaan hak atas tanah adat.   The integration of values through the original methods of indigenous communities not only presents values that are visibly distinct but also felt differently compared to the integration of values through state methods, which may result in a reduction of the original values. This article aims to analyze the integration of 'krik slamat' values in the exercise of rights over customary land. The research method employed is a non-doctrinal research method with an anthropological legal approach and a conceptual approach. The article demonstrates that 1) 'Krik slamat' values are a legal principle with a dimension of divinity ('religio magis') serving as the foundational basis for the formation of customary law ('pulung'), and 2) The integration of 'krik slamat' values into customary law is carried out through the 'pera telu' method, ensuring that these values remain visible and palpable within the legal principles and norms of customary law related to the exercise of rights over customary land.